2018
DOI: 10.1007/s10157-018-1599-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of xanthine oxidase inhibitor in patients with chronic heart failure complicated with hyperuricemia: a prospective randomized controlled clinical trial of topiroxostat vs allopurinol—study protocol

Abstract: The Excited-UA study would provide novel evidence for the clinical relevancy of xanthine oxidoreductase inhibitor treatment in patients with chronic heart failure and hyperuricemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The estimated study completion date is December 2020. 3) A prospective randomized clinical trial with allopurinol versus topiroxostat (another XO inhibitor) in patients with chronic heart failure is currently ongoing in Japan (Sakuma et al, 2018). Nonpurine xanthine oxidase inhibitors have been developed to avoid the many side effects of allopurinol, but none has quite matched it in terms of efficacy.…”
Section: Pharmacological Modulation Of Rosmentioning
confidence: 99%
“…The estimated study completion date is December 2020. 3) A prospective randomized clinical trial with allopurinol versus topiroxostat (another XO inhibitor) in patients with chronic heart failure is currently ongoing in Japan (Sakuma et al, 2018). Nonpurine xanthine oxidase inhibitors have been developed to avoid the many side effects of allopurinol, but none has quite matched it in terms of efficacy.…”
Section: Pharmacological Modulation Of Rosmentioning
confidence: 99%
“…A positive coefficient indicates that it is positively correlated with the enzyme activity, while a negative number indicates that it is negatively correlated with the enzyme activity. The IC 50 for XO activity increased with increasing peak areas of 3,4,7,10,11,16,17,18,20,21,23,24,25,26,27,28, and 30, indicating that this component group was positively correlated with XO inhibitory activity and that peaks 1,2,5,6,8,9,12,13,14,15,19,22,31,32, and 33 were negatively correlated with their inhibitory activities ( Figure 6). Variable importance in projection (VIP) scores is important indicators that reflect the ability of independent variables to explain dependent variables.…”
Section: Plsr Analysis Resultsmentioning
confidence: 98%
“…These methods enable rapid analysis, complement their respective advantages, and can be used to comprehensively evaluate the quality of L. lucidum. GRA showed that the main components responsible for the XO inhibitory activity of L. lucidum might be characteristic peaks 1,2,4,5,6,7,8,9,11,12,14,15,16,17,20,21,23,25,27,28,29,31,32, and 33. PLS analysis showed that peaks 1, 2, 4, 5, 6, 7, 14, 17, 22, 24, 25, 28, 31, F I G U R E 6 Effect coefficient of each chromatographic peak on the xanthine oxidase inhibitory activity F I G U R E 7 VIP contribution of each characteristic peak to the antioxidant activity of Ligustrum lucidum and 33 had significant effects on the XO inhibitory activity.…”
Section: Plsr Analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations